2020
DOI: 10.3389/fpsyg.2020.543933
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Expressions in English and Spanish: Influence of Typology and Metaphorical Construal

Abstract: This study investigates how typological and metaphorical construal differences may affect the use and frequency of temporal expressions in English and Spanish. More precisely, we explore whether there are any differences between English, a satelliteframed language, and Spanish, a verb-framed language, in the use of certain temporal linguistic expressions that include a spatial, deictic component (Deictic Time), a purely temporal relation between two events (Sequential Time) or the expression of the duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Time as metaphoric expressions has been studied rigorously in many languages, including English. There have been some studies focusing on space as the metaphoric expression of time (Ahrens & Huang, 2002;Boroditsky, 2000) and comparing time expressions in English with other languages, e.g., Chinese (Chen, 2014), Spanish (Valenzuela & Alcaraz Carrión, 2020). Boroditsky (2000) Valenzuela & Alcaraz Carrión (2020) also suggested that English more frequently uses deictic expressions with directional language than Spanish.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Time as metaphoric expressions has been studied rigorously in many languages, including English. There have been some studies focusing on space as the metaphoric expression of time (Ahrens & Huang, 2002;Boroditsky, 2000) and comparing time expressions in English with other languages, e.g., Chinese (Chen, 2014), Spanish (Valenzuela & Alcaraz Carrión, 2020). Boroditsky (2000) Valenzuela & Alcaraz Carrión (2020) also suggested that English more frequently uses deictic expressions with directional language than Spanish.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The studies of time collocations are rarely done, especially in the EFL settings. Although several studies have concerned the comparison of time expressions in the L1 and English as the target language (e.g., Chen, 2014;Golfam et al, 2019;Valenzuela & Alcaraz Carrión, 2020), little is known about the familiarity of EFL learners towards collocations of time which is also important in mastering the target language since time expressions are basic expressions in daily life.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In other words, the way one conceptualizes time may be revealed by such manual movements. For instance, an increasing number of studies on speakers' temporal gestures have shown that across cultures and languages people conceptualize time differently (e.g., Casasanto & Jasmin, 2012;Cooperrider and Núñez, 2009;Gu, Mol et al, 2017;Gu, Zheng et al, 2019a;Kita et al, 2001;Le Guen & Pool Balam, 2012;Núñez & Sweetser, 2006;Sullivan & Bui, 2016;Valenzuela & Carrión, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Li (2015) explored the phraseology behavior of the noun time and figured out some patterns of metaphorical mappings, such as TIME IS MONEY, TIME IS MOTION, etc. Research on time expressions has also been conducted to examine other languages, usually in comparison to the English language, such as Chen (2014), Fuhrman et al (2011), Golfam et al (2019), Valenzuela & Alcaraz Carrión (2020). These studies compare time orientation and time expressions in several languages proving that each language and each culture has distinctive ways of describing time-related concepts.…”
Section: Introductionmentioning
confidence: 99%